2020
DOI: 10.1177/1359105320974431
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from emotional intelligence to well-being and health outcomes among unemployed: Mediation by health-promoting behaviours

Abstract: This study investigated whether health-promoting behaviours mediate the relationship between emotional intelligence (EI) and well-being and health outcomes in the unemployed population. Spanish unemployed (N = 530) completed questionnaires of EI, health-promoting lifestyles, subjective well-being and perceived health. Path-analytic results showed that EI predicted well-being and self-reported health. Health-promoting behaviours: spiritual growth, stress management and physical activity, partially mediated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Compare to self-employed occupation, unemployed people were found negatively associated with spiritual growth. This is similar with other results among unemployed people [ 45 , 46 ]. Lastly, residents with higher monthly family incoming levels had significantly higher HPLP scores on nutrition, spiritual growth, interpersonal relations and stress management.…”
Section: Discussionsupporting
confidence: 93%
“…Compare to self-employed occupation, unemployed people were found negatively associated with spiritual growth. This is similar with other results among unemployed people [ 45 , 46 ]. Lastly, residents with higher monthly family incoming levels had significantly higher HPLP scores on nutrition, spiritual growth, interpersonal relations and stress management.…”
Section: Discussionsupporting
confidence: 93%
“…Mediation analysis further showed that self-rated health partially mediated the relationship between Internet use and civil servants’ well-being; therefore, it indicated that Internet use affects civil servants’ self-rated health and, thus, their happiness. This study found that health has a significant positive correlation with both Internet use and happiness, with Internet use improving the health of civil servants and, subsequently, their happiness; this finding coincides with Ni and Pelaez-Fernandez [ 65 , 66 ]. This positive correlation can be attributed to the fact that information on health and medical care, online purchase of medications and other health-related queries are more easily accessible via the Internet, which influences their lifestyles, including eating habits and physical exercise.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, there is general consensus, across different clinical and nonclinical samples and using different methodological approaches to EI measurement, that EI is negatively related to depression, suggesting that EI might be a protective factor against depression [ 13 , 23 ]. Specifically, recent research on unemployment and health has shown that EI plays a key role in reducing negative psychological symptoms associated with unemployment, including depression, and in boosting well-being [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%